Manual for production of Chamo strain Nile tilapia fingerlings and preparation of fish feeds from locally available material - Abate, Tewodros; Getahun, Abebe; Geremew, Akewake; Ambaw, Gebermedihin; Recha, John W.M. (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2020)
Climate change has resulted in increased local temperatures that in turn have increased evapotranspiration, and negatively affected the breeding grounds of several important fish species due to reduction in the water levels of water bodies (Ficke et al. 2007). The rise in local temperature also affects the physico-chemical properties of water, including temperature, pH, dissolved oxygen, salinity, and concentration of different ions in water bodies (El Morhit & Mouhir 2014). These changes negatively affect the physiological (e.g. reproduction) and behavioral dynamics of fish as well as their natural feed leading to lower production of capture fish (Chabot & Guénette 2013).